Analysis of the Indonesian Government's Policy on High Rice Prices Amid Abundant Supply from the Perspective of Islamic Economics - Satrio Agung Subekti; Muhajirin Muhajirin; Atmo Prawiro (Universitas KH. Abdul Chalim Mojokerto, 2026)
The persistent rise in rice prices in Indonesia, despite an ample national stock, highlights a disconnect between food availability and affordability, thereby threatening the nation's food security. This paper explores the root causes of rice price fluctuations, evaluates the effectiveness of distribution mechanisms, and analyzes how Islamic economic principles especially the insights of Imam Ibn Taymiyyah and Imam Ibn Qayyim al-Jawziyyah can inform effective policy responses. Utilizing a literature review approach, the study draws upon data related to rice production, distribution channels, and pricing trends, while also incorporating a normative analysis rooted in the Maqashid Shariah framework. The analysis identifies key contributors to inflated rice prices, including inefficient distribution networks, market control by dominant entities (oligopoly), and weak pricing regulations. Within the Islamic economic paradigm, these issues represent a departure from the ideals of justice and societal welfare. Classical Islamic thinkers advocated for state involvement in price regulation (tas’ir), the prohibition of hoarding (ihtikar), and the fair distribution of resources as mechanisms for safeguarding public interests. Policy recommendations include modernizing agricultural production, enhancing distribution efficiency through targeted subsidies, and reinforcing government regulation in the marketplace to promote price stability and ensure the well-being of both producers and consumers.